Legal Politics in the Perspective of the 1945 Constitution of the Republic of Indonesia - Mukhlis Achmad; Muh. Ramli; Armawansya; Riyan Adnan Wahyudi; Aslan Syah Mattulanreng (Masterpiece, 2026)
Legal politics constitutes the fundamental state policy that determines the direction, substance, and implementation of law in order to achieve national objectives. In the Indonesian constitutional system, the 1945 Constitution of the Republic of Indonesia serves as the supreme legal foundation guiding the formulation and development of national legal politics. This study examines legal politics from the perspective of the 1945 Constitution and analyzes its implications for the formation of national law. Employing a normative legal research method, this study applies statutory, conceptual, and historical approaches by analyzing constitutional provisions, legislation, legal doctrines, and scholarly opinions. The findings reveal that the 1945 Constitution provides normative guidance and clear limitations for national legal politics, particularly in upholding the principles of the rule of law, democracy, constitutional supremacy, and the protection of human rights. The Constitution not only functions as the highest legal norm but also as a philosophical and juridical framework that directs legal policy toward achieving justice, legal certainty, and social welfare. Furthermore, legal politics grounded in constitutional values significantly influences the substance of legislation, the legislative process, and mechanisms of constitutional review. A constitutional-oriented legal politics ensures that laws are formulated in a democratic, participatory, and accountable manner while remaining consistent with the objectives of the state as stipulated in the Preamble of the 1945 Constitution. Therefore, strengthening constitutional compliance in legal politics is essential to develop a just, responsive, and socially equitable national legal system in Indonesia